Between earth and water: a wooden snake figurine from the Neolithic site of Järvensuo 1. (August 2021) - Koivisto, Satu; Lahelma, Antti
Abstract: Abstract : Figurines made of wood, bone, amber, clay and lithics are occasionally discovered in prehistoric contexts in Fennoscandia, but the discovery, in 2020, of a unique wooden snake figurine during the excavations of a Neolithic wetland site in Finland broadens our understanding of the worldview of northern peoples 4400 years ago.